Epidemiology of Fabry disease in patients in hemodialysis in the Madrid community. - Corchete Prats, Elena; González-Parra, Emilio; Vega, Almudena; Macías, Nicolás; Delgado, María; Fernández, Milagros; Jesús Sánchez, Rafael; Álvarez, Laura; Jesús Miranda, Ramón; Vian, Javier; López, Virginia; Mérida, Evangelina; et al. (Nefrología)
This study screened for Fabry disease (FD) in patients in hemodialysis (HD) in the region of Madrid (CAM) with a cross-sectional design to evaluate HD-prevalent patients, followed by a three-year period prospective design to analyze HD-incident patients. Inclusion criteria: patients older than 18 years on HD in the CAM, excluding patients diagnosed with any other hereditary disease with renal involvement different from FD, that sign the Informed Consent (IC). Exclusion criteria: underaged patients or not agreeing or not being capable of signing the IC. Results: 3470 patients were included, 63% males and with an average age of 67.9 ± 9.7 years. 2357 were HD-prevalent patients and 1113 HD-incident patients. For HD-prevalent patients, average time in HD was 45.2 months (SD 51.3), in HD-incident patients proteinuria was present in 28.4%. There were no statistical differences in plasmatic alpha-galactosidase A (α-GAL-A) activity or Lyso-GL-3 values when comparing HD-prevalent and HD-incident populations and neither between males and females. A genetic study was performed in 87 patients (2.5% of patients): 60 male patients with decreased enzymatic activity and 27 female patients either with a decreased GLA activity, increased Lyso-Gl3 levels or both. The genetic variants identified were: p.Asp313Tyr (4 patients), p.Arg220Gln (3 patients) and M290I (1 patient). None of the identified variants is pathogenic. Conclusions: 76% of HD Centers of the CAM participated in the study. This is the first publication to describe the prevalence of FD in the HD-population of a region of Spain as well as its average α-GAL-A-activity and plasmatic Lyso-Gl3 levels. It is also the first study that combines a cross-sectional design with a prospective follow-up design. This study has not identified any FD patient.